SEDIMENT FERTILITY BASED MANAGEMENT OF AQUACULTURE IN URBAN AND RURAL PONDS OF CHHATTISGARH - Roy, K (Journal of the Inland Fisheries Society of India, 2020)
A survey was conducted to determine the nutrient and fertility status of pond bottom soil in a few perennial urban ponds and some perennial rural ponds of Raipur, Chhattisgarh to assess their fisheries production potential.Results revealed that the ponds of the region are characterized by moderate soil available-N content, low soil available-P content, high soil exchangeable K content, moderate level of organic carbon and near neutral to mildly alkaline pH. There is a significant imbalance in soil N:C and N:P ratios. The ponds in this region are moderately productive and there exists ample scope to enhance the current level of production through adoption of soil based management packages. Urban ponds need lime (as CaCO3) @700-800 kg/ha/yr., Nitrogen (as N) @200 kg/ha/yr., Phosphorus (as P2 O5) @100kg/ha/yr. and Organic C (as cow dung) @8000-10000 kg/ha/yr. Rural ponds require lime (as CaCO3 ) @500 kg/ha/yr.,Nitrogen (as N) @150 kg/ha/yr., Phosphorus (as P2 O5) @125 kg/ha/yr. and Organic C (as cow dung) @8000-10000 kg/ ha/yr. These soil amendments are necessary in order to make the ponds optimally suitable for semi intensive fishculture practices. Rural ponds are better in sediment nutrient status than urban counterparts. Key words: Ponds, fisheries productivity, bottom soil, management, aquaculture